Lion & lamb - Patterson, James, 1947-; Swierczynski, Duane (New York : Little, Brown and Company, 2023)
Rival PIs, Veena Lion and Cooper Lamb work the same intense headline-making case involving an Eagles starting quarterback and his even more famous wife, a Grammy-winning singer, and together, knowing every secret in Philadelphia, prove how two wrongs can make a right.
Keywords: Murder investigation -- Fiction; Private investigators -- Fiction; Football players -- Fiction; Women singers -- Fiction; Philadelphia (Pa.) -- Fiction; Large type books; Detective and mystery fiction; Thrillers (fiction)